2008
DOI: 10.1073/pnas.0807691105
|View full text |Cite
|
Sign up to set email alerts
|

Pten null prostate tumorigenesis and AKT activation are blocked by targeted knockout of ER chaperone GRP78/BiP in prostate epithelium

Abstract: GRP78/BiP has recently emerged as a novel biomarker for aggressive prostate cancer. Here, we report that homozygous deletion of Grp78 specifically in mouse prostate epithelium suppresses prostate tumorigenesis without affecting postnatal prostate development and growth. Mouse prostates with double conditional knockout of Grp78 and Pten exhibit normal histology and cytology, in contrast to the invasive adenocarcinoma in mouse prostates with Pten inactivation. AKT activation in Pten null prostate epithelium is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
187
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(200 citation statements)
references
References 28 publications
13
187
0
Order By: Relevance
“…Chemical inhibition of AKT suppressed both human and murine ADM (44). Previous studies of GRP78 and Pten-null-induced prostate cancer and leukemia revealed that GRP78 haploinsufficiency potently suppressed AKT activation mediated by loss of PTEN in these cancers (21,22). Subsequently, it was demonstrated that the cell-surface form of GRP78 (scGRP78) complexes with PI3K to promote phosphatidylinositol (3-5)-trisphosphate formation (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical inhibition of AKT suppressed both human and murine ADM (44). Previous studies of GRP78 and Pten-null-induced prostate cancer and leukemia revealed that GRP78 haploinsufficiency potently suppressed AKT activation mediated by loss of PTEN in these cancers (21,22). Subsequently, it was demonstrated that the cell-surface form of GRP78 (scGRP78) complexes with PI3K to promote phosphatidylinositol (3-5)-trisphosphate formation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of DNA from the mouse tail or pancreas was performed by PCR. Primers for detection of the Pdx1-Cre and floxed or knockout alleles for Grp78 and p53 were described previously (21,57). To determine if recombination of the Kras G12D lox-stop-lox cassette occurred, DNA was extracted from pancreas and PCR was performed following the protocol described from the Jacks Lab (https://jacks-lab.mit.edu/protocols/genotyping/ kras_cond).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, EnR stress-induced signalling to apoptosis via CASPASE-4/12 [94,95] or the IRE1 -JNK pathway may be important. GRP78 knockdown is also known to induce apoptosis by blocking AKT activation in colon, PTEN-null leukaemia and prostate cancer cell lines [88,96,97]. Hence, it will be important to measure the effect of knocking down GRP78 on AKT signalling in LCC9 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human tumor cells indeed exhibit evidence of ER stress, and reduced capacity to elicit an UPR within malignant cells results in decreased tumorigenesis in model systems (Ma and Hendershot, 2004;Bi et al, 2005;Fu et al, 2008;Luo and Lee, 2013). Xbp1 has been considered protumorigenic sustained, augments tumor formation in both an inflammatory (i.e., CAC after DSS/AOM) and noninflammatory (i.e., CRC in Apc min mice) context.…”
Section: Isc Expansion Is Individually Determined In Each Xbp1-deficimentioning
confidence: 99%